If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10(y + -1) = -2(6 + y) Reorder the terms: 10(-1 + y) = -2(6 + y) (-1 * 10 + y * 10) = -2(6 + y) (-10 + 10y) = -2(6 + y) -10 + 10y = (6 * -2 + y * -2) -10 + 10y = (-12 + -2y) Solving -10 + 10y = -12 + -2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2y' to each side of the equation. -10 + 10y + 2y = -12 + -2y + 2y Combine like terms: 10y + 2y = 12y -10 + 12y = -12 + -2y + 2y Combine like terms: -2y + 2y = 0 -10 + 12y = -12 + 0 -10 + 12y = -12 Add '10' to each side of the equation. -10 + 10 + 12y = -12 + 10 Combine like terms: -10 + 10 = 0 0 + 12y = -12 + 10 12y = -12 + 10 Combine like terms: -12 + 10 = -2 12y = -2 Divide each side by '12'. y = -0.1666666667 Simplifying y = -0.1666666667
| 3.14(36)(18)= | | -9(-2-8g)= | | -40=-5Y | | 2x^2+19x=32 | | 5x+7-4x=-21 | | 5x-24+3x+36=35+6x-2 | | 2x+5y=17-4x | | 18=v+20 | | 9c+10=100 | | U/3-7=-2 | | N+(n+2)+(n+4)=171 | | 6m^2+7x=5 | | 7X-4X+3=2X-8 | | 7(9b+6)= | | y+4x=14 | | (3-2x)=14 | | 6x-16=16-2x | | 5x+2(x-6)=4(x+1)-3 | | 2x+4=10+5 | | 9n=536 | | 7=2+t | | 8x+40=90 | | -9(6f-3)= | | 13c-90=5c-34 | | 8/24=6/n | | 7.6(x-2.25)=-15.2 | | 6(10-5x)=45-5(5x+1) | | 64x^2+16x=1 | | 5m-20=4m+16 | | -9(7y-2)= | | 2-3a=8-2(2a+7) | | 2x+3+(2y-2)yi=0 |